2023
DOI: 10.1039/d3nh00235g
|View full text |Cite
|
Sign up to set email alerts
|

Atomically precise AuxAg25−x nanoclusters with a modulated interstitial Au–Ag microenvironment for enhanced visible-light-driven photocatalytic hydrogen evolution

Abstract: Herein, we report the study of atomically precise AuxAg25-x nanoclusters (NCs) toward photocatalytic hydrogen evolution. The incorporation of Au atoms into Ag25 NCs not not only narrowed the HOMO-LUMO gaps...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Our group prepared a series of 25 metal atom NCs protected by the same ligand and used them for photocatalytic H 2 production. 72 Besides the staggered type-II energy levels between NCs and anatase TiO 2 , surface catalytic reactions should be considered. Ab initio Density Functional Theory (DFT) calculations in this work revealed that the calculated Bader charges of H* for hydrogenabsorbing metal sites on the surfaces of alloyed Au x Ag 25−x NCs were more negative than those in single metal counterparts.…”
Section: ■ Surface Catalytic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group prepared a series of 25 metal atom NCs protected by the same ligand and used them for photocatalytic H 2 production. 72 Besides the staggered type-II energy levels between NCs and anatase TiO 2 , surface catalytic reactions should be considered. Ab initio Density Functional Theory (DFT) calculations in this work revealed that the calculated Bader charges of H* for hydrogenabsorbing metal sites on the surfaces of alloyed Au x Ag 25−x NCs were more negative than those in single metal counterparts.…”
Section: ■ Surface Catalytic Reactionsmentioning
confidence: 99%
“…NC-1, NC-2, and NC-3 represent x values of 1 ≤ x ≤ 3, 3 ≤ x ≤ 8, and 19 ≤ x ≤ 23, respectively. Reproduced with permission from refs and . Copyright 2021 American Chemical Society; 2023, Royal Society of Chemistry.…”
Section: Surface Catalytic Reactionsmentioning
confidence: 99%
“…Metal nanoclusters (NCs) have emerged as a noteworthy class of nanomaterials, showcasing distinct properties attributable to the quantum connement effect when compared to their nanoparticle counterparts. [1][2][3][4] Wet chemistry approaches enable the preparation of metal NCs under ambient pressure on a gram scale. 5,6 Typically, this synthesis involves the reduction of metal salts or precursors in the presence of protecting ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] With the advancement of sophisticated characterization techniques, numerous metal clusters with atomiclevel resolved structures have been reported to date. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] It has been observed that the metal core of many of these clusters shares the same polyhedral units, despite variations in peripheral ligands or metal-ligand motif structures. These polyhedral units encompass an M 13 centered icosahedron, [22][23][24][25][26][27][28] an M 6 octahedron, [29][30][31][32][33][34][35] an M 13 cuboctahedron 36 and an M 7 decahedron, [37][38][39][40][41][42] among others, where 'M' represents Au, Ag, Cu, or other metal atoms or their mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The Wang group reported an Au cluster, [Au 24 (CuCPh) 14 (PPh 3 ) 4 ](SbF 6 ) 2 , which contains two cuboctahedral units by sharing of faces. 36 Additionally, the assembly of octahedral units by sharing vertices has been observed in Ag clusters such as Ag 23 (PPh 3 ) 8 (SC 2 H 4 Ph) 18 , 29 [Ag 38 (SPhF 2 ) 26 (PR′ 3 ) 8 ] and [Ag 63 (SPhF 2 ) 36 (PR′ 3 ) 8 ] + (HSPhF 2 = 3,4-difluorothiophenol and R′ = alkyl/aryl). 32 Recently, Wang et al reported the largest structurally characterized cluster of clusters to date, [Ag 93 (PPh 3 ) 6 (CuCR) 50 ] 3+ (R = 4-CH 3 OC 6 H 4 ).…”
Section: Introductionmentioning
confidence: 99%